2013
DOI: 10.1210/jc.2012-3104
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of the Autonomic Nervous System Predicts the Development of the Metabolic Syndrome

Abstract: Context:Stress is suggested to lead to metabolic dysregulations as clustered in the metabolic syndrome. Although dysregulation of the autonomic nervous system is found to associate with the metabolic syndrome and its dysregulations, no longitudinal study has been performed to date to examine the predictive value of this stress system in the development of the metabolic syndrome.Objective: We examined whether autonomic nervous system functioning predicts 2-year development of metabolic abnormalities that consti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
68
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(83 citation statements)
references
References 92 publications
8
68
1
6
Order By: Relevance
“…This may indicate that possible shared pathophysiological aspects involved. For instance, higher baseline parasympathetic nervous system activity and shortened telomere length have been associated with worsening metabolic dysregulation after 2 years in NESDA participants 18, 61…”
Section: Discussionmentioning
confidence: 99%
“…This may indicate that possible shared pathophysiological aspects involved. For instance, higher baseline parasympathetic nervous system activity and shortened telomere length have been associated with worsening metabolic dysregulation after 2 years in NESDA participants 18, 61…”
Section: Discussionmentioning
confidence: 99%
“…We measured respiratory sinus arrhythmia (RSA), a form of heart rate variability (HRV) determination which is regarded as a marker for the status of the vegetative nervous system. It has been shown that RSA is reduced in patients with major depression compared to controls (Licht et al, 2008(Licht et al, , 2013. A recent meta-analysis has demonstrated an association between increasing depression severity and lower HRV (Kemp et al, 2010;Licht et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Por otra parte, la RI se define como una disminución a la respuesta fisiológica a la insulina por parte de los tejidos, particularmente a nivel del tejido muscular y adiposo 27 . Si se considera a la obesidad y el sobrepeso como la característica principal de la muestra del presente estudio, se presume que existe un estilo de vida poco saludable, caracterizado por el desbalance entre el gasto y el consumo calóri-co, constituyendo una serie de factores de riesgo para el desarrollo de anormalidades metabólicas, disautonomía y síndrome metabólico 7,28 . Sumado a esto, existen estudios epidemioló-gicos que han demostrado que la obesidad y RI, se asocian con un incremento de la FC de reposo debido a un estímulo adrenérgico 20 .…”
Section: Discussionunclassified
“…La obesidad ha sido asociada a alteraciones en la función del Sistema Nervioso Autónomo (SNA), demostrando la existencia de una alteración del balance autonómico sobre el nódulo sinusal [2][3][4] . La disautonomía ha sido frecuentemente mencionada como nexo causal entre un estilo de vida poco saludable y el desbalance energético, el sedentarismo y anormalidades metabólicas como lo evidencia el síndrome metabólico [5][6][7] . En sujetos obesos se ha demostrado una disminución de la actividad vagal asociada a un mayor riesgo de enfermedad coronaria 8 .…”
Section: Análisis De Variabilidad Del Ritmounclassified